Enzyme-aided extraction of sulfated polysaccharides from Turbinaria turbinata brown seaweed - Hammed, Ademola Monsur; Jaswir, Irwandi; Senay, Simsek; Alam, Md Zahangir; Amid, Azura (Universiti Putra Malaysia, 2017)
This study involves extraction of sulfated polysaccahride (SP) from brown seaweed (Turbinaria turbinata). Eight processing conditions affecting enzyme aided extraction (EAE) were screened using Plackett-Burman design. Three signifcant factors (hydrolysis time, enzyme concentration and extraction stage) were optimized using Faced Centred Central Composite Design in Random Surface Methods. Micrograph obtained using Field Emission Scanning Electron Microscopy revealed that cellulase degradation ruptured the seaweed cell matrix thus caused an increase in the release of SP. The optimum conditions for extraction of SP from T. turbinata are: extraction stage of 2, hydrolysis time of 19.5 h and enzyme concentration of 1.5 μl/ml to produce 25.13% yield. The SP obtained from cellulase treated T. turbinata is a suitable anti-inﬂammatory agent for pharmaceutical applications.